Widespread and transgenerational retrotransposon activation in inter‐ and intraspecies recombinant inbred populations of Lotus japonicus. (30th July 2022) - Fukai, Eigo; Yoshikawa, Manabu; Shah, Niraj; Sandal, Niels; Miyao, Akio; Ono, Seijiro; Hirakawa, Hideki; Akyol, Turgut Yigit; Umehara, Yosuke; Nonomura, Ken‐Ichi; Stougaard, Jens; Hirochika, Hirohiko; et al.
SUMMARY: Transposable elements (TEs) constitute a large proportion of genomes of multicellular eukaryotes, including flowering plants. TEs are normally maintained in a silenced state and their transpositions rarely occur. Hybridization between distant species has been regarded as a 'shock' that stimulates genome reorganization, including TE mobilization. However, whether crosses between genetically close parents that result in viable and fertile offspring can induce TE transpositions has remained unclear. Here, we investigated the activation of long terminal repeat (LTR) retrotransposons in three Lotus japonicus recombinant inbred line (RIL) populations. We found that at least six LTR retrotransposon families were activated and transposed in 78% of the RILs investigated. LORE1a, one of the transposed LTR retrotransposons, showed transgenerational epigenetic activation, indicating the long‐term effects of epigenetic instability induced by hybridization. Our study highlights TE activation as an unexpectedly common event in plant reproduction. Significance Statement: In this study, we show that hybridization between closely related inter‐ and intraspecies parents that result in viable and fertile offspring can cause widespread and transgenerational long terminal repeat (LTR) retrotransposon activation in Lotus japonicus, highlighting that the activation of transposable elements (TEs) is likely to occur frequently during normal plant reproduction.